Chronic Obstructive Pulmonary Disease and the Cardiovascular System: Vascular Repair and Regeneration as a Therapeutic Target - Karnati, Srikanth; Seimetz, Michael; Kleefeldt, Florian; Sonawane, Avinash; Madhusudhan, Thati; Bachhuka, Akash; Kosanovic, Djuro; Weissmann, Norbert; Krüger, Karsten; Ergün, Süleyman (Frontiers in Cardiovascular Medicine, 2021)
Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide and encompasses chronic bronchitis and emphysema. It has been shown that vascular wall remodeling and pulmonary hypertension (PH) can occur not only in patients with COPD but also in smokers with normal lung function, suggesting a causal role for vascular alterations in the development of emphysema. Mechanistically, abnormalities in the vasculature, such as inflammation, endothelial dysfunction, imbalances in cellular apoptosis/proliferation, and increased oxidative/nitrosative stress promote development of PH, corpulmonale, and most probably pulmonary emphysema. Hypoxemia in the pulmonary chamber modulates the activation of several transcription factors and signaling cascades, which propagates inflammation and infiltration of neutrophils, resulting in vascular remodeling. Endothelial progenitor cells have angiogenesis capabilities, resulting in transdifferentiation of the smooth muscle via aberrant activation of several cytokines, growth factors, and chemokines. The vascular endothelium influences the balance between vaso-constriction and -dilation in the heart. Targeting key players affecting the vasculature might help in the development of new treatment strategies for both PH and COPD. The present review aims to summarize current knowledge about vascular alterations and production of reactive oxygen species in COPD. The present review emphasizes on the importance of the vasculature for the usually parenchyma-focused view of the pathobiology of COPD.